Comparative evaluation of the use of acidic additives on sewage sludge composting quality improvement, nitrogen conservation, and greenhouse gas reduction. (December 2018) - Pan, Junting; Cai, Hanzhen; Zhang, Zengqiang; Liu, Hongbin; Li, Ronghua; Mao, Hui; Awasthi, Mukesh Kumar; Wang, Quan; Zhai, Limei
Highlights: Effects of six different acidic additives on sewage sludge composting were studied. All additions increased compost N conservation through reducing NH3 volatilization. Elemental sulphur and phosphoric acid caused high N2 O loss and low quality of compost. Calcium superphosphate addition resulted in high compost salinity. Apple pomace, citric acid and MgH2 PO4 benefit the compost quality improvement. Abstract: The aim of this study was investigated the effects of acidic additives apple pomace (AP), citric acid (CA), elemental sulphur (ES), phosphoric acid (PA), magnesium hydrogen phosphate (PM), and calcium superphosphate (CP)) on N conservation and greenhouse gas (GHG) emissions during sewage sludge composting. Results showed that adding the additives have no negative effects on compost hygienisation, but could improve the N conservation. Treatments with additives showed 2.56–5.48% N loss of initial N, which is lower than the control (9.73%). Compared to other compost products, ES- and PA-treatments had the lower NH3 volatilizations (0.80% and 0.98% of initial N, respectively) and germination index values (0.52 and 0.74, respectively), while the higher N2 O emissions (2.48% and 2.29% of initial N, respectively) and salinities. Comprehensive evolution of N loss, GHG emissions and compost maturity in this study, the feasibility of using AP, CA, and PM in high-quality compost production is promising.